2019
DOI: 10.1007/s40258-019-00542-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Extended and One-Time Screening Versus No Screening for Non-Valvular Atrial Fibrillation in the USA

Abstract: Background There is limited evidence on the clinical and cost benefits of screening for atrial fibrillation (AF) with electrocardiogram (ECG) in asymptomatic adults. Methods We adapted a previously published Markov model to evaluate the clinical and economic impact of one-time screening for non-valvular AF (NVAF) with a single 12-lead ECG and a 14-day extended screening with a hand-held ECG device (Zenicor single-lead ECG, Z14) compared with no screening. Clinical events considered included ischemic stroke, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Other studies have suggested both clinical and cost‐effectiveness of AF screening using traditional modalities such as pulse palpation, 12‐lead ECG, and patch monitoring. 32 , 34 In our analysis, we found that pulse palpation followed conditionally by 12‐lead ECG resulted in similar QALY estimates as no screening, and screening using 12‐lead ECG alone generally resulted in reduced QALYs. Given the multitude of possible AF screening approaches and the generally low stroke rates among individuals with detected AF, conducting well‐powered randomized trials comparing each strategy is infeasible.…”
Section: Discussionmentioning
confidence: 54%
“…Other studies have suggested both clinical and cost‐effectiveness of AF screening using traditional modalities such as pulse palpation, 12‐lead ECG, and patch monitoring. 32 , 34 In our analysis, we found that pulse palpation followed conditionally by 12‐lead ECG resulted in similar QALY estimates as no screening, and screening using 12‐lead ECG alone generally resulted in reduced QALYs. Given the multitude of possible AF screening approaches and the generally low stroke rates among individuals with detected AF, conducting well‐powered randomized trials comparing each strategy is infeasible.…”
Section: Discussionmentioning
confidence: 54%
“…ICER in this study reported $ 58,728 in the 12-lead ECG mode and $ 47,949 in the Z14. The study also reported that screening the general population at age 75 for NVAF was cost-effective on the threshold of willingness to pay of $ 100,000 [42].…”
Section: Discussionmentioning
confidence: 86%
“…In this study, the nal cost and ICER with 12-lead ECG were equal to $ 188484860 and 6129.59, respectively. Furthermore, the nal cost and ICER with Z14 were equal to $ 65.4848194 and 77.49967, respectively [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 54 Given our focus on wearable devices, we did not directly evaluate handheld 1L ECG, although we observed that a similar combination of pulse palpation followed by 12L ECG was on the cost-effectiveness frontier with comparable ICERs. More recently, Oguz et al 55 found that 1-time screening using 12L ECG alone followed by 14-day screening with patch monitor at 75 years of age was also cost-effective. In general, our findings support previous observations suggesting that AF screening can be cost-effective, and they provide new evidence that strategies using wearable devices may be economically favorable.…”
Section: Discussionmentioning
confidence: 99%